A feasibility study of individual 3D-printed navigation template for the deep external fixator pin position on the iliac crest - Bin Liang; Qiang Chen; Shuai Liu; Shuo Chen; Qingqiang Yao; Bo Wei; Yan Xu; Cheng Tang; Liming Wang (BMC Musculoskeletal Disorders, 2020)
Abstract Background The aim of this study was to investigate the feasibility of an individual navigation template for the deep pin position on the iliac crest, based on digital design and 3D printing technology. Methods The preoperative CT images of 8 patients with pelvic fractures were collected. The data were reconstructed using a 3D imaging reconstruction workstation. An individual navigation template for the deep pin position on the iliac crest was designed on a virtual 3D model. The individual drill template and the solid pelvic model were produced using the 3D printing technology. The individual drill template was used for intraoperative deep pin position on the iliac crest after the preoperative simulation was completed. Results Thirty-two external fixator pins were inserted using the individual drill template. The average depth of pins was 84.82 mm. The trajectories were appropriate based on the postoperative X-ray and CT scan. No significant difference in the entry point, convergence angle, and caudal angle of the pins were noted before and after the operation (all P > 0.05). Finite element analysis indicated that the deep external fixator pin position could more reasonably distribute the stress in the cortical and spongy bones in the pelvis. All patients could perform partial weight-bearing activity 6 weeks postoperatively. No loosening and rupture of the pin, infection, and no damage of blood vessels and nervous tissue were found during the entire follow-up period. Conclusions The individual drill template technique is an improvement of the traditional technique, which could increase precision and the depth of pin position. In addition, good mechanical stability and low risk of pin-related complications occurred due to the individual drill template, which makes the external fixation technique a potential alternative.